Evidence of interspersed co-existing CaCO3-III and CaCO3-IIIb structures in polycrystalline CaCO3 at high pressure. (April 2014) - Merlini, M.; Crichton, W. A.; Chantel, J.; Guignard, J.; Poli, S.
Abstract: New experimental data are reported on high-pressure polymorphism of CaCO3 . The CaCO3 -III phase was stabilized using a large-volume press device and high-resolution X-ray powder diffraction (XRPD) patterns were collected from a few mm 3 of powder sample. The interpretation of XRPD indicates that CaCO3 -III and CaCO3 -IIIb structures are present simultaneously and are in similar proportions. The lack of any unindexed peaks demonstrates that these two polymorphs are the only phases in this experiment, indicating that CaCO3 -III and CaCO3 -IIIb are the structures most likely to occur above 2.5 GPa. Relevant co-axial crystallographic matrix transformations from lower-pressure polymorphs to both CaCO3 -III and CaCO3 -IIIb are discussed to illustrate a further possible occurrence of co-existing and interspersed stable polymorphs in carbonate systems.